Enhancing the postgraduate research culture and community - Billot, JM; Jones, M; Banda, M (Higher Education Research and Development Society of Australasia (HERDSA), 2013)
During the last two decades, there have been significant changes within the New Zealand tertiary sector due to Government, stakeholder and community demands. The result has been an altered context for learning and a need for continual reassessment of the learning environment. This paper discusses a case study that used survey and focus group data to uncover the concerns and issues faced by postgraduate research students in relation to developing and enhancing a research culture. Moreover, since a student will engage with tertiary study both cognitively and emotionally, the focus was on how the students identified their own needs within their research experience. As a university’s particular context frames and supports the development of its research culture, student voices were deemed to best represent the student experience of the research community. Our study identifies that the student research experience is shaped by the support and interactions that they encounter. Coded and thematically analysed qualitative data was combined with the quantitative data to ascertain those characteristics of a research context which students identify as significant. This paper focuses on the qualitative results. Findings indicate that student engagement is enhanced when they feel part of a wider research community and have a sense of belonging. We claim that where synergies exist between student aspirations and the institutional culture in which they study, subcultures develop and there is a greater likelihood that positive outcomes will ensue. These findings have implications for the strategic development of the university’s research culture and the ongoing development of supportive initiatives for research students in relation to higher degree research and enhancing teaching and learning.
Keywords: Postgraduate research student experience; Research culture; Community of practice